ROLE OF MUSLIM INTELLECTUALS IN THE DEVELOPMENT OF SCIENTIFIC THOUGHT - Yasmeen Mahnaz Faruqi (Jurnal Ilmiah Peuradeun, 2015)
The education systems adopted by the most of the Islamic countries have been based on ‘so-called secular Western education’. Consequently a cultural dichotomy is observed in their societies between a traditional Islamic education on the one hand restricted to religious groups, and a secular Western education in main stream schools, colleges and universities. This paper presents a discussion regarding the role that Muslim scholars played in the development of scientific thinking in the Middle Ages. It argues that the Muslims were not just the preservers of the ancient and Greek knowledge, but that they contributed original works to the different fields of science. They were inspired by the Islamic view of nature that is, mankind had a duty to ‘study nature in order to discover God and to use nature for the benefit of mankind’. This knowledge was transferred to Western Europe and subsequently played an important role in revitalizing a climate of learning and exploration in Europe, leading to the Renaissance in the sixteenth and seventeenth centuries.